Providing Opportunities to Learn in Home-Based Child Care Settings: Observations of Learning Contexts and Behavior. Issue 6 (18th August 2017) - Rusby, Julie C.; Crowley, Ryann; Jones, Laura B.; Smolkowski, Keith
ABSTRACT: Research Findings : This observation study investigated the prevalence and correlates of learning contexts provided to preschool-age children in 133 registered child care homes in below-average-income neighborhoods in the U.S. Pacific Northwest. On average, 30% of the observed proportion of time was spent in structured teacher-led activities, 51% in free-choice activities, 10% in routine activities, 1% in watching video/TV, and 7% in transition. Home-based child care providers gave significantly more positive recognition during structured teacher-led activities, and children engaged in more prosocial behavior during free-choice time. Directives and noncompliance occurred more often during transitions. A higher child-to-caregiver ratio was associated with more time spent in free-choice time, and caregiver experience and education were not associated with the time spent in specific learning contexts. Practice or Policy : Similar to preschool and center-based child care, current practice in home-based child care is to offer a mix of structured teacher-led and free-choice activities. To facilitate young children's skill development within these learning activities typically offered, it is necessary to increase research and provide empirically based professional development opportunities relevant to home-based child care settings. Attention to home-based child care will likely reach many young children and be particularly beneficial for those in low-income households.